2022
DOI: 10.1093/clinchem/hvac151
|View full text |Cite
|
Sign up to set email alerts
|

MALDI–TOF–MS for Rapid Screening and Typing of β-Globin Variant and β-Thalassemia through Direct Measurements of Intact Globin Chains

Abstract: Background Traditional phenotype-based screening for β-globin variant and β-thalassemia using hematological parameters is time-consuming with low-resolution detection. Development of a MALDI–TOF–MS assay using alternative markers is needed. Methods We constructed a MALDI–TOF–MS-based approach for identifying various β-globin disorders and classifying thalassemia major (TM) and thalassemia intermedia (TI) patients using 901 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…To resolve overlapping peaks and improve accuracy, high resolution MS (HRMS) can be employed for specific cases [18] , [19] . The quality of spectral data and the selection of appropriate regions for deconvolution contribute to the precision of mass measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To resolve overlapping peaks and improve accuracy, high resolution MS (HRMS) can be employed for specific cases [18] , [19] . The quality of spectral data and the selection of appropriate regions for deconvolution contribute to the precision of mass measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, mass spectrometry (MS), a powerful analytical technique, has been used in research laboratories to identify hemoglobin variants based on the intact mass information of the variant globin chain [11] , [12] , [13] . However, the use of MS in clinical diagnostic laboratories has been mainly limited to low-resolution MS for quantification of small molecules [14] , [15] and peptides [16] , [17] , while high-resolution MS and Matrix Assisted Laser Desorption Ionization - Time-of-Flight (MALDI-ToF) MS have been explored for analyzing intact protein diagnostic markers [18] , [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Before our study, two new variants were found which appears to have the same molecular trace than as our variant: Hb Dongguan-Dongcheng found in healthy individuals during population screening for Hb Pathies in China with a MALDi-ToF method 5 and, Hb Wanjiang, discovered studying an asymptomatic patient. 6 Hb Wanjiang is supposed to arises from a double recombination event as Hb Palencia (γ-δ-β fusion gene). 7 Therefore, Hb Yogoupon appears to be a new case of the same mutant but in an African background without Chinese admixture.…”
mentioning
confidence: 99%